Challenges and Management of Acute Coronary Syndrome in Cancer Patients - Costa, Isabela Bispo Santos da Silva; Andrade, Fernanda Thereza de Almeida; Carter, Diego; Seleme, Vinicius B.; Costa, Maycon Santos; Campos, Carlos M.; Hajjar, Ludhmila Abrahão (Frontiers in Cardiovascular Medicine, 2021)
Cancer and cardiovascular disease are the leading causes of mortality in the world. The prevalence of cardiovascular risk factors and coronary artery disease in cancer patients is elevated, and it is associated with high mortality. Several mechanisms, such as the proinflammatory and procoagulant states present in cancer patients, may contribute to these scenarios. Oncological therapy can predispose patients to acute thrombosis, accelerated atherosclerosis and coronary spasm. Treatment decisions must be individualized and based on the cancer history and balancing bleeding and thrombosis risks.